Features of the joint use of visible-range satellite and satellite radar data for monitoring arctic icebergs based on data from Franz Josef Land area - I. A. Bychkova; E. V. Platonova; V. G. Smirnov; И. А. Бычкова; Е. В. Платонова; В. Г. Смирнов (Государственный научный центр Российской Федерации Арктический и антарктический научно-исследовательский институт, 2023)
Given the availability of data, in order to monitor icebergs in the vast Arctic region, it is necessary to ensure an optimal ratio of the satellite radar data cost (with a wide swath and high spatial resolution) and the reliability of the results obtained. The aim of the study was to evaluate the effectiveness of using only non-commercial satellite information for monitoring icebergs. To achieve this goal, an iceberg detection technique was applied based on statistical criteria of searching for gradient zones in analyzing two-dimensional fields of satellite images. As a source of information, we used high spatial resolution satellite data obtained from non – commercial satellites Sentinel-1 (radar data) and Landsat-8 (visible spectral range data) with a pixel size of 40 × 20 and 15 m, respectively.Through comparison with the data of the visible spectral range of ultra-high resolution, the error was estimated of measuring the size of icebergs using the visible range equipment of the Landsat-8 satellite and the radar of the Sentinel-1 satellite. Based on the analysis of satellite data of the visible spectral range and radar data, the spatial dimensions of icebergs formed by the outlet glaciers of Franz Josef Land n 2020–2022 were estimated. The materials were collected for the period August-September, corresponding to the conditions of minimum ice extent in the Franz Josef Land area and sufficient natural illumination for using the data of the visible spectral range in the Arctic. In total, about 100 satellite images were analyzed. The sources of error in the satellite measurements are discussed, as well as the reasons for the impossibility in some cases to identify Franz Josef Land icebergs on radar images. It is shown that the largest contribution to the iceberg runoff of Franz Josef Land is made by outflow glaciers located on Georg Land, Wilczek Land, Gall, Salisbury and Champa islands. According to the results of the study, it is concluded that radar data with a pixel size of 40 m allow one to obtain ...